EVALUATION OF CUSTOMERS' PROFITABILITY IN THE ACCOUNTING PRACTICE OF TUZLA CANTON COMPANIES (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The aim of the paper is to clarify and systematize the methods of evaluating customers’ profitability on a scientifically based methodology. It also aims at investigating the relationship between business results achieved by individual sectors in the companies from the Tuzla Canton (TC) and the applied method of profitability management, in the function of generating such results. The analysis was conducted on the appropriateness of the current approach to profitability management according to information resources which served as the basis of the approach. Certain limitations were identified, which in practice lead to an inaccurate evaluation of customers’ profitability. The transitional economy, characterized by macroeconomic instability and a low competitiveness factor in general, along with other numerous external limitations, requires that companies effectively rearrange their value chain, in the function of finding internal resources, in order to achieve long-term profitability of the customer portfolio management. The origin of modern trends in creation and maintenance of comparative advantages of the company lies in adoption of the “Customer Relationship Management” (CRM) business philosophy. The research results indicate insufficient knowledge of the management about the key “drivers” of success in achieving comparative advantages and point to inadequate organization of the accounting function which is not able to support a modern approach to business performance management. Keywords: Profitability management, customers’ profitability evaluation methods, sectorial analysis of business indicators, transition economy, Tuzla Canton